FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENCEGAHAN HIV/AIDS PADA REMAJA KOMPLEK PERUMAHAN AJUEN DESA LAM HASAN KECAMATAN PEUKAN BADA KABUPATEN ACEH BESAR TAHUN 2008 - Fahdhienie, Farrah (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2011)
Farrah Fahdhienie1, Desvita, SKM, M. Kes2Peminatan Epidemologi, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245Peminatan Kesehatan Lingkungan, Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, Banda Aceh, 23245 Abstract The cases of HIV/AIDS increased significantly in Aceh started from one case in year 2004 to 30 cases with 16 died in 2007. It is necessary to increase the prevention of adolescene from HIV/AIDS because they are vulnerable to the disease. They have strong curiosity and would like to try something new such as sexual activities which can directly infect HIV/AIDS to them. The goals of this study are to find out the factors related to prevention of HIV/AIDS by adolescence. This is a descriptive analytic study with cross-sectional design. The population of this study is all 210 adolescence at the age of 14-24 years. The study had 68 samples by using questionnaire. Chi-square statistical test and Yates correction were used to analyze data to find out the relationship between independent variables and dependent variable. The result of the study indicated that there were relationship between knowledge (the results of x2 test is 4.35); role of parents (the results of x2 test is 5.29) and prevention of HIV/AIDS. It is suggested to the District Health Office of Aceh Besar and PUSKESMAS to improve extension acticities on HIV/AIDS to community.Keywords: prevention of HIV/AIDS, deadly disease, adolescent knowledge